Optimasi Proses Ekstraksi Daun Sirsak (Annona muricata L) Metode MAE (Microwave Assisted Extraction) Dengan Respon Aktivitas Antioksidan Dan Total Fenol - aulia, latifa putri (JURNAL AGROINDUSTRI HALAL, 2018)
Soursop leaf (Annona muriciata L) contain active ingredients that is annonain, saponin, flavonoid, and tannin. Some research even found that in soursop leaf contain bio active substance called acetogenin that act as anti cancer. Commonly extraction process used to extracting substance in the leaf is known as conventional extracting process which has flaws. Hence its need further research in term of extracting in which more optimal that is the usage of microwave (Microwave Assisted Extraction / MAE) MAE extraction is extracting process that using microwave radiation to heat the solvent quick and efficient so the extraction can be done in time to extract selectively from various raw ingredients. Response Surface Methodolgy (RSM) is a an appropriate method to analyze the effects of a single variable and for seeking the optimum condition for multivariable systems efficiently. The purpose of this research is to determine the optimal condition from soursop leaf extraction using MAE extraction with 2 variables that is extraction time and solvent ratio so can be concluded that rough soursop leaf extract with the optimal phenol and characteristics anti oxidant activities. This research using CCD method from RSM (Response Surface Methodology) with 2 unbound variables that time extraction (X1) and solvent ratio (X2). Earned result from this research is quadratic with the equation is a value for antioxidant activity Y = -2,24087 + 2,17790X1 + 5,25566X2 + 0,12000X1X2 - 0,25875X12 – 0,12373X22. While the total value for phenol is Y = -175,82270 – 8,07421X1 + 42,0810X2 – 2,62317X1X2 – 3,00785X12 -1,39204 X22. The optimum point from each variable is the extracting time 9' and 84" with solvent ratio of 25,19 of ingredient that is simplicia powder of soursop leaf approximately 25gr. From the optimum point we can drawn that optimum condition of anti oxidant activity respond is as much as 75,75% and phenol total value of 276,9 ppm. From the analysis result we can conclude that extracting time and solvent ratio can signnificanly effect the result we get.